CIRCOMONCOBOTHRIUM KOPARGAONENSIS N. SP. FROM FRESHWATER FISH CLARIAS BATRACHUS (JERDON 1849) FROM GODAVARI RIVER AT KOPARGAON, DISTRICT AHMEDNAGAR, INDIA - DANDAWATE, R. R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
The present study deals survey of cestode parasites from freshwater fishes like Clarias batrachus (Jerdon, 1849) from Godavari river at Kopargaon in district Ahmednagar during April 2012 to December 2013.The present communication deals with the new species kopargaonensis from the genus Circomoncobothrium is having Scolex is large, pear shaped, Cirrus pouch placed in anterior half of the segment, obliquely placed, submarginally oval in shape, opens at the distal end by a common genital pore, ovary is distinctly bilobed, large in size transversely placed near the posterior margin of the segment, Vitellaria are follicular and cortically arranged placed in a line pre-ovarian.